Recommendations for improving the quality of the interdisciplinary medical care of grown-up with congenital heart disease (GUCH) - Kaemmerer, Harald; Bauer, Ulrike; de Haan, Fokko; Flesch, Julia; Gohlke-Bärwolf, Christa; Hagl, Siegfried; Hess, John; Hofbeck, Michael; Kallfelz, Hans Carlo; Lange, Peter E.; Nock, Hermine; Schirmer, Karl Robert; et al. (International journal of cardiology, 2011)
Background/objectives - The number of adult congenital heart disease (ACHD) patients will be larger in the medium to long term than that of children and adolescents with congenital heart disease. The present structures for the medical care of ACHD patients are not sufficient and need to be improved. Therefore the task force's assignment and objective was to develop recommendations for the structure of the interdisciplinary medical care of adults with congenital heart disease (GUCH). - Methods - The members of the interdisciplinary task force were selected on the basis of their special clinical, scientific and organizational expertise. Initially, a sub-group of the interdisciplinary task force compiled a draft version of these recommendations, with reference to international recommendations. It was circulated and then agreed with all task force members in two joint meetings. The recommendations were then submitted to the relevant committees of all participating societies and groups and approved following detailed discussion. - Results - With the publication of this document the interdisciplinary task force considers its first task as completed. - Conclusions - The compiled recommendations for the structure of the interdisciplinary medical care of adults with congenital heart disease (GUCH) should ensure that the structural and medical pre-conditions for comprehensive GUCH medical care are created.